Pengaruh Merek, Kemasan dan Harga Terhadap Keputusan Pembelian Bolen Pisang Marwah - Devi Anggriani (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the brand, packaging, and price on purchasing decisions of Marwah Banana Bolen. The data of this study were obtained through the method of presenting data and the results of respondents' responses (questionnaires). The statistical analysis used in this study is multiple linear analysis using SPSS version 20.0. This research is quantitative research that connects two or more variables to study, describe, reveal and see the influence between the variables formulated on the research hypothesis. The number of samples in this study was 96 consumers of banana Marwah Bolen. The data were collected through a Likert scale and analyzed statistically with the t-test and F-test. It is hoped that this research can be input for producers so that they can find out that consumers make purchasing decisions based on brand, packaging, and price.